Geospatial Analysis and Turbidity Measurement for Monitoring Suspended Solid of Hitotsuse Dam in Miyazaki Prefecture, Kyushu, Japan - Santosa, Purnama Budi; Mitani, Yasuhiro (Forum Geografi, 2015)
The existence of suspended solids at Hitotsuse dam, Miyazaki Prefecture, Kyushu, Japan, has been the main concern of Kyushu Electric Power Company. These have been carried by rivers flowing into the dam. In a long term, it is worried that this phenomenon will potentially cause the environmental degradation, especially around the dam, where the Kyushu Electric Power Plant is located. Therefore, necessary measures are required to protect the dam from environmental degradation, which in return is to assure its long term power plant operational. Preliminary studies found that the suspended solid, which was generated upstreams and was carried out into the dam by rivers, causes the turbid water resident. Therefore, evaluation on the potential sources of the existence of the suspended solids needs to be carried out. In this research, analysis was conducted to understand the spatial distribution and the quantity of the suspended solid. For this purpose, by focusing attention on the upper river basin of reservoir, several factors which are possible to cause turbid water are extracted and analyzed quantitatively by using GIS. To understand the characteristic of the river turbidity, river flows and river turbidity are measured at several selected stations. Then mechanical factors causing turbid water are identified after analyzing relationship between efflux characteristics and possible factors of suspended solids. The results show that spatial information extraction could be done efficiently by applying spatial analysis method. Furthermore, by applying multiple regression analysis, it was found that landslide scars, artificial forests, drainage area, and terrain undulation are indicated as the dominant factors causing the turbidity.